Abu Bakar and the Conspiracy to Revive the Ancient Empire: Searching for Legitimacy in Johor-Pahang Relations - Abdullah, A Rahman Tang (Paramita: Historical Studies Journal, 2023)
This article examines Abu Bakar’s involvement in other Malay states regarding the relations between Johor and Pahang in the 19th century. It argues that his ultimate aim was to consolidate his position in Johor’s territory and obtain recognition from other Malay rulers. This is because the existing view claims that Abu Bakar had the ambition to restore the ancient empire of Johor-Riau-Lingga under his hegemony. Indeed, this view is generalised by historians even though it remains merely speculative. Thus, the discussion here is to provide a conclusive argument that rejects this view by showing that his involvement in other Malay states' political affairs was to consolidate his position in Johor.Keywords: Abu Bakar, Johor, Pahang, Ancient Empire, Legitimacy  Artikel ini mengkaji keterlibatan Abu Bakar di negara-negara Melayu lainnya terkait hubungan Johor dan Pahang pada abad ke-19. Dikatakan bahwa tujuan utamanya adalah untuk mengkonsolidasikan posisinya di wilayah Johor dan mendapatkan pengakuan dari penguasa Melayu lainnya. Sebab pandangan yang ada mengklaim bahwa Abu Bakar berambisi mengembalikan kerajaan kuno Johor-Riau-Lingga di bawah hegemoninya. Memang, pandangan ini digeneralisasikan oleh para sejarawan meskipun masih bersifat spekulatif belaka. Dengan demikian, pembahasan di sini adalah untuk memberikan argumen konklusif yang menolak pandangan ini dengan menunjukkan bahwa keterlibatannya dalam urusan politik negara-negara Melayu lainnya adalah untuk mengkonsolidasikan posisinya di Johor.Kata kunci: Abu Bakar, Johor, Pahang, Kerajaan Kuno, Legitimasi